Работы на стоянке Мира в 2009 г. - Степанчук, В.Н.; Писарев, И.Б.; Ветров, Д.А.; Беленко, Н.Н.; Зайцев, В.А. (Археологічні дослідження в Україні, 2010)
In 2009, at the multilayer Palaeolithic site Mira (Zaporizzhya Region) the research of areas adjacent to the entrance zone of dwelling structure I was ongoing. New data on microstratigraphy was obtained, spatial structure of cultural remains localization was specified, additional series of stone artefacts and fauna remains were found, and samples for natural science methods analysis were taken.